Reduced ultrafine particle levels in São Paulo’s atmosphere during shifts from gasoline to ethanol use - Alberto Salvo (Nature Portfolio, 2017)
The biofuel ethanol has been introduced into urban transportation in many countries. Here, by measuring aerosols in São Paulo, the authors find that high ethanol prices coincided with an increase in harmful nanoparticles by a third, as drivers switched from ethanol to cheaper gasoline, showing a benefit of ethanol.